PERTANGGUNGJAWABAN PIDANA ORANG TUA DALAM SISTEM PERADILAN ANAK: PERGESERAN PARADIGMA MENUJU PERTANGGUNGJAWABAN BERSAMA DALAM HUKUM PIDANA INDONESIA - Suci Ramadhani Putri; Irpan Suriadiata (GEMOVE: Journal of Gender, Movement, and Empowerment, 2025)
The Indonesian juvenile justice system, regulated under Law No. 11 of 2012 on the Juvenile Criminal Justice System, fails to establish parental criminal liability for offenses committed by minors. This legal vacuum has resulted in high recidivism rates and undermines the rehabilitative goals of juvenile justice. This study aims to analyze the necessity of establishing parental criminal liability in Indonesia's juvenile justice system, examine comparative models from Japan, Germany, and Canada, and propose a comprehensive framework for shared accountability between juveniles and their parents. Using qualitative normative-comparative legal research, this study develops the Theory of Dual Accountability in Juvenile Justice, which posits that criminal liability should be shared between the juvenile offender and negligent parents through proportional criminal sanctions, administrative penalties, and rehabilitative interventions. The findings demonstrate that Japan's Family Court system, Germany's parental responsibility model, and Canada's restorative justice approach all incorporate mechanisms that hold parents accountable for supervisory negligence. This study proposes amendments to Indonesia's Juvenile Justice Law to introduce three tiers of parental criminal liability: (1) criminal sanctions for gross negligence resulting in serious juvenile crimes, (2) administrative penalties for moderate supervisory failures, and (3) mandatory rehabilitative programs for minor cases. The proposed framework balances punitive measures with family rehabilitation, ensuring that both juveniles and parents bear proportional responsibility for criminal conduct. This paradigm shift toward shared accountability represents a fundamental reform in Indonesian criminal law, recognizing that effective juvenile crime prevention requires legal mechanisms that compel parental responsibility alongside juvenile rehabilitation.